2022
DOI: 10.3390/physiologia2010001
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Parameters and Iron Status in Adult Men and Women Using Altitude Adjusted and Unadjusted Hemoglobin Values for Anemia Diagnosis in Cusco, Peru (3400 MASL)

Abstract: (1) Background: Current diagnosis of anemia in high altitude populations uses an adjustment of observed hemoglobin (Hb) values. Such an approach has been challenged by findings in different populations in Tibet, Ethiopia and the Andes as inappropriate, as it might incorrectly classify an individual with complete iron stores as anemic. We aimed to assess the suitability of this approach in adult men and women from Cusco, Peru (3400 m); (2) Methods: Complete blood count and iron status biomarkers were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
0
8
0
1
Order By: Relevance
“…Compared to non-pregnant women, SpO 2 increased with gestation at 3600 m [ 25 ]. In Cusco at 3400 m, the mean SpO 2 in non-pregnant women was 91.06% [ 17 ], a value that is lower than that observed in pregnant women living in the same place (94.91%), while the average value of SpO 2 at 150 m in non-pregnant women was 98.41%, which did not vary later during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to non-pregnant women, SpO 2 increased with gestation at 3600 m [ 25 ]. In Cusco at 3400 m, the mean SpO 2 in non-pregnant women was 91.06% [ 17 ], a value that is lower than that observed in pregnant women living in the same place (94.91%), while the average value of SpO 2 at 150 m in non-pregnant women was 98.41%, which did not vary later during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Life at HA has been associated with decreased uterine artery blood flow, increased utero-placental resistance, alterations in the expression of placental factors, chronic hypoxia, and changes in vascularity and has been implicated in a variety of adverse pregnancy outcomes including intrauterine growth restriction, low birth weight infants, intrauterine fetal demise, and preeclampsia [ 16 ]. It is assumed that high Hb at HA is not associated with iron deficiency (ID) in adult men and women [ 17 ]; however, no studies have been conducted to evaluate serum ferritin, serum transferrin receptor (sTfR), and serum hepcidin levels during pregnancy at HA.…”
Section: Introductionmentioning
confidence: 99%
“…The number of participants ranged from 66 to 804, with a total of 4522 high-altitude residents and with a predominance of women and children. Five studies evaluated only women of reproductive age [ 20 , 21 , 22 , 23 , 24 ], one study evaluated postpartum women [ 25 ], four studies included infants [ 24 , 26 , 27 , 28 ], and three studies evaluated the general population [ 29 , 30 , 31 ]. Regarding the altitude where the studies were conducted, we found six studies that included populations located between 1000 and 2500 m [ 20 , 21 , 22 , 32 , 33 ], four studies that included populations located between 2500 and 3500 m [ 25 , 26 , 29 , 30 , 32 ], and seven studies that evaluated populations located above 3500 m [ 23 , 24 , 27 , 28 , 29 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 included studies, 3 [ 21 , 27 , 32 ] assessed the role of Hb in the diagnosis of anemia at an altitude using ROC curves. The reference standard (ID marker) most frequently evaluated was ferritin in 11 studies [ 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 33 ], followed by TBI in 4 studies [ 22 , 24 , 29 , 32 ], sTFR in 3 studies [ 21 , 22 , 24 ], and transferrin saturation in 3 studies [ 22 , 23 , 25 ]. The cutoff points for these markers were similar between studies according to the age of the population but with heterogeneity when adjusting for inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation